HUBUNGAN PEMBELAJARAN BERBASIS MASALAH MELALUI EKSPERIMEN TERHADAP MOTIVASI DAN HASIL BELAJAR FISIKA GAYA DAN GERAK MAHASISWA PROGRAM STUDI GEOLOGI UNIVERSITAS OTTOW GEISSLER PAPUA - Tipawayel, Theophilus K. (Jurnal Ilmu Pendidikan Indonesia, 2015)
The aim of study would be: (1) to identify the problem-based learning model through experiment methods toward Physics Learning Results on the subject of gravity an motion (2) to understand the relation of problem-based learning mode through experiment methods towards the results of learning physics on the subject of gravity and motion of geology study programmes scholars of University Ottow Geissler Papua. Variable definition studied is made through the relation in problem-based mode by experiment method, scholars would find scientific knowledge more useful to science particularly on the concept of grafity an motionin the newton rules. The sampling was using the technique of non-probability sampling that is number of sample is 15 scholars which is the setiated sampling if population members were used. Analyzing method used is the quantitative. The study resulted in the rate of r count > r table ( 0,6721 > 0,514 ) correlative coefficient determinant ( r2) of 45 % learning motivation variable and the remaining 55 % by other factor(s). it should be concluded that rb = 0,8 and r table = 0,553 then the decision of rb > r table would mean reliable which means the category has a strong significant and relation between the problem-based learning mode through experiment method towards learning motivation. Key word(s) : Experiment Method, Learning Motivation, Learning Results, Force and Movement.